African commitments for agricultural development: Goals and milestones for Mozambique - Chitiga, Margaret; Fofana, Ismaël; Diallo, Mariam Amadou (International Food Policy Research Institute, 2020)
Mozambique is a signatory to the Comprehensive Africa Agriculture Development Programme (CAADP) and the 2014 Malabo Declaration on Accelerated Growth and Transformation for Shared Prosperity and Improved Livelihoods that commit the country to achieve a 6% annual agricultural growth rate, 10% agricultural expenditure share, ending hunger and halving poverty. Additionally, Mozambique has signed the African Union Agenda 2063 and has committed to achieving the Sustainable Development Goals (SDGs). A Results Framework is applied to address the CAADP/Malabo, SDGs and Agenda 2063 goals to translate Mozambique’s agricultural development agenda into tangible outcomes. The framework utilizes an economy-wide general equilibrium model and a microsimulation model which are linked in a sequential manner. The modelling results reveal that the Business as Usual (BaU) growth strategy is insufficient to meet the goals of the three agendas. Hence, other paths that might yield better results are investigated. The analysis then investigates the impacts of the prioritization of agriculture sub-sectors and commodities, and agricultural value-chain investment strategies. The results show that public investment-led productivity increases in agriculture contribute more across all the indicators on the production and consumption side. Indeed, agriculture contributes more than industry and services to number of jobs created, food expenditure and consumption expenditure growth, and the same as industry to gross domestic product growth. The investments are best financed by budget constraint and external financing, which bring about positive impacts on socioeconomic outcomes when compared to the BaU. The analysis further reveals agricultural commodities with the highest contribution to agricultural development. This information is then used to design an accelerated agricultural investment strategy. Results from this scenario show that Mozambique makes substantial progress in meeting the commitments of the three agendas and this allows to provide recommendations for a successful agricultural investment planning, design and implementation for the country.